Mepiquat Poisoning – Report of a Patient with Mepiquat Poisoning Presenting with Bradycardia and Hypoglycemia - Smitesh Gutta; Ramya I; Karthik Gunasekaran; Arun Jose (Institute of Medico-legal Publications Pvt Ltd, 2021)
Mepiquat chloride is a quaternary ammonium salt which is used as a plant growth regulator. We reportthe case of 18 year old tribal girl who had consumed Mepiquat chloride (5%) in an attempt of deliberateself-harm. The patient had symptomatic bradycardia and hypoglycaemia at presentation both resolved withsupportive treatment. Unlike Chlormequat which can be fatal in humans when ingested mepiquat whichlacks the choline subunit and has only a weak effect on the muscarinic and nicotinic receptors in the humanbody causing only mild bradycardia and hypoglycemia. Patient has been followed up for 1 year and shedoing well with no sequelae.